INVESTIGATING YOUNG LEARNERS PERCEPTION AND MORAL VALUES ON LISTENING SKILL THROUGH WATCHING MOVIE “DORA: THE LOST CITY OF GOLD” - Ina Rohiyatussakinah; Sri Ardiani; Ida Nuraida; Nur Hidayanti (Journal of English Language Teaching and Literature (JELTL), 2022)
The aim of the research was to investigate young learners perceptions and moral values on listening while English language teaching for young learner by having "Dora: The Lost Gold City" Movie at SMP Daarul Yaqiin. Method of research used descriptive analysis to explore young learner’s perception and moral values. Instrument used were observation, questionnaires and interviews. Interviews and questionnaires were conducted in the seventh grades of SMP Daarul Yaqiin. It was followed by 50 young learners who join listening class. The results of this study indicate; (1) Young learners give a good perception about the use of the movie "Dora: The lost city of gold" (2) Young learners give positive feedback to attract listening skills by using the movie "Dora: The lost city of gold" in learning, and (3) young learners get moral values by watching the movie "Dora: The lost city of gold". The advantages of using the movie "Dora: The lost city of gold" in learning listening are; it helps young learners understanding the subject easily, young learners were happy, gave them motivation to learn English for young learner. From these finding the conclusion was the used of the movie "Dora: The lost city of gold" in English listening easy understanding material has positive response from young learners and also provided several benefits for them especially moral values for young learners.